Dynamic characteristics of a COVID-19 outbreak in Nanjing, Jiangsu province, China - Wang, Junjun; Ma, Tao; Ding, Songning; Xu, Ke; Zhang, Min; Zhang, Zhong; Dai, Qigang; Tao, Shilong; Wang, Hengxue; Cheng, Xiaoqing; He, Min; Du, Xuefei; et al. (Frontiers in Public Health, 2022)
Objectives: SARS-CoV-2 lineage B.1.617.2 (also named Delta variant) was declared as a variant of concern by WHO. This study aims to describe the outbreak that occurred in Nanjing municipal city triggered by the Delta variant through the epidemiological parameters and to understand the evolving epidemiology of the Delta variant. Methods: We collected data of all COVID-19 cases in the outbreak from July 20, 2021, to August 24, 2021, and estimated the distribution of serial interval, basic and time-dependent reproduction number (R0 and Rt), and household secondary attack rate (SAR). We also analyzed the cycle threshold (Ct) values of infections. Results: A total of 235 cases have been confirmed. The mean value of serial interval was estimated as 4.79 days with Weibull distribution. The R0 was 3.73 (95% confidence interval [CI], 2.66-5.15) estimated by the exponential growth method. The Rt decreased from 4.36 on July 20 to below 1 on August 1 estimated by the Bayesian approach. We estimated the household SAR as 27.35% (95%CI, 22.04%-33.39%), and the median Ct value of open reading frame 1ab (ORF1ab) genes and nucleocapsid protein (N) genes as 25.25 (interquartile range [IQR], 20.53-29.50) and 23.85 (IQR, 18.70-28.70), respectively. Conclusions: Delta variant is more aggressive and transmissible than the original virus types. Continued non-pharmaceutical interventions are still needed.